Contemporary rends in high-dose interleukin-2 use for metastatic renal cell carcinoma in the United States - TİNAY, İLKER (ELSEVIER SCIENCE INC, 2015)
Background: Targeted therapies (TTs) have revolutionized metastatic renal cell carcinoma (mRCC) treatment in the past decade, largely replacing immunotherapy including high-dose interleukin-2 (HD IL-2) therapy. We evaluated trends in HD IL-2 use for mRCC in the IT era. Methods: Our cohort comprised a weighted estimate of all patients undergoing HD IL-2 treatment for mRCC from 2004 to 2012 using the Premier Hospital Database. We assessed temporal trends in HD IL-2 use including patient. disease, and hospital characteristics stratified by era (pre-TT uptake: 2004-2006, uptake: 2007-2009, and post-TT uptake: 2010-2012) and fitted multivariable regression models to identify predictors of treatment toxicity and tolerability. Results: An estimated 2,351 patients received HD IL-2 therapy for mRCC in the United States from 2004 to 2012. The use decreased from 2004 to 2008. HD IL-2 therapy became increasingly centralized in teaching hospitals (24% of treatments in 2004 and 89.5% in 2012). Most patients who received HD IL-2 therapy were men, white, younger than 60 years, had lung metastases, and were otherwise healthy. Vasopressors, intensive care unit admission, and hemodialysis were necessary in 53.4%, 33.0%, and 7.1%, respectively. Factors associated with toxicities in multivariable analyses included being unmarried, male sex, and multiple metastatic sites. African Americans and patients with single-site metastases were less likely to receive multiple treatment cycles. Conclusions: HD IL-2 therapy is used infrequently for mRCC in the United States, and its application has diminished with the uptake of TT. Patients are being increasingly treated in teaching hospitals, suggesting a centralization of care and possible barriers to access. A recent slight increase in HD IL-2 therapy use likely reflects recognition of the inability of TT to effect a complete response. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: High-dose interleukin-2; Immunotherapy; Renal cell carcinoma; Kidney cancer; Therapy trends; Toxicity; INTERFERON-ALPHA; DOUBLE-BLIND; CANCER; STATISTICS; SURVIVAL; ANTIBODY; MELANOMA; SAFETY